The effect of profitability and liquidity on tax avoidance - Indy, Listia Aulia; Lamsah, Lamsah (Institute of Accounting Research and Novation (IARN), 2024)
This study explains the phenomenon that occurred in 2019, which is suspected of carrying out tax avoidance practices. The purpose of this study is to reveal the effect of profitability and liquidity on tax avoidance. The population in this study was mining sector companies in the coal production sub-sector listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The results of the study indicate that profitability has an effect on tax avoidance and liquidity has no effect on tax avoidance.